Developing Worksheet Based on Creative Problem-Solving Models - Baiq Fatmawati; Sitti Rohmi Djalilah; Nurul Wafiah (Jurnal Penelitian Pendidikan IPA, 2023)
The focus of this research is to develop worksheets on biology content for the eleventh graders in high school. The development research research design included the following steps: research and information collection, planning, develop preliminary form of product, preliminary field testing, and main product revision. The participant are 12 students in the initial product trial for the eleventh graders of SMA N 1 Suralaga in the school year of 2021/2022. Using a closed questionnaire to gather research data and student worksheets covering the eleventh-grade material, such as the movement system, blood circulation, digestion, respiration, excretion, coordination, and psychoactive substances, to assess the validity of the instrument supplied to experts and students. Analyzing the outcomes of expert instrument validation, determining the average value, and using percentages to group the results into five categories—very bad, not good, good enough, good, and very good—represent quantitative descriptive data analysis. It was discovered from the limited test results that the implementation indicator received the lowest percentage in the extremely unfavorable category during the development at the initial product test stage were the very bad category (85.7%) and very not good (14.3%). Development indicators; good enough (28.6%) and good (71.4%). Ideate indicators; 100% very good. Clarify indicator; very not good (14.3%), not good (28.6%), good enough (42.6%), and very bad (14.2%). It can be concluded that it was necessary to revise the initial product, namely by including in more detail the components of the creative problem solving indicator both at clarify, ideate, develop, and implement